Outcomes of HIV treatment from the private sector in low-income and middle-income countries: a systematic review protocol. Issue 1 (8th January 2020) - Mburu, Gitau; Igbinedion, Ewemade; Lim, Sin How; Paing, Aung Zayar; Yi, Siyan; Elbe, Stefan; Mwai, Grace W
Abstract : Introduction: Private sector provision of HIV treatment is increasing in low-income and middle-income countries (LMIC). However, there is limited documentation of its outcomes. This protocol reports a proposed systematic review that will synthesise clinical outcomes of private sector HIV treatment in LMIC. Methods and analysis: This review will be conducted in accordance with the preferred reporting items for systematic review and meta-analyses protocols. Primary outcomes will include: (1) proportion of eligible patients initiating antiretroviral therapy (ART); (2) proportion of those on ART with <1000 copies/mL; (3) rate of all-cause mortality among ART recipients. Secondary outcomes will include: (1) proportion receiving Pneumocystis jiroveci pneumonia prophylaxis; (2) proportion with >90% ART adherence (based on any measure reported); (3) proportion screened for non-communicable diseases (specifically cervical cancer, diabetes, hypertension and mental ill health); (iv) proportion screened for tuberculosis. A search of five electronic bibliographical databases (Embase, Medline, PsychINFO, Web of Science and CINAHL) and reference lists of included articles will be conducted to identify relevant articles reporting HIV clinical outcomes. Searches will be limited to LMIC. No age, publication date, study-design or language limits will be applied. Authors of relevant studies will be contacted for clarification. Two reviewers will independently screen citations and abstracts, identify full text articles for inclusion, extract data and appraise the quality and bias of included studies. Outcome data will be pooled to generate aggregative proportions of primary and secondary outcomes. Descriptive statistics and a narrative synthesis will be presented. Heterogeneity and sensitivity assessments will be conducted to aid interpretation of results. Ethics and dissemination: The results of this review will be disseminated through a peer-reviewed scientific manuscript and at international scientific conferences. Results will inform quality improvement strategies, replication of identified good practices, potential policy changes, and future research. PROSPERO registration number: CRD42016040053.